A qualitative research on patient care management in Malaysian hospitals; patients and doctors experiences of bedside care / Susan Thomas - Susan, Thomas (2013)

(untitled)
Over the past decade there has been an exponential increase of tertiary level specialized care to meet the needs of the population in Malaysia. The organisation structure of MOH which encompasses the three levels of the health care delivery system, which are Federal, State and District levels, demonstrates decentralization and efficiency. This system is changing towards wellness service that emphasizes a lifetime health plan in keeping the child and family well. For centuries the traditional practice demonstrated by doctors has been a system of inquiry which consists of close-ended questions that fulfil the doctors’ need in collecting information. This process has been part of the medical curriculum for years and had little concern of how patients felt and understood information. In a multicultural country like Malaysia, patients come from different background, race, religion and languages. Lack of information poses as a barrier in the quality of care provided. Patients may not fully comprehend their disease and may make the wrong decision. This research is significant because there are limited studies exploring patient care management in public hospitals in Malaysia Therefore the purpose of the ethnographic research was to explore the experiences of patients and doctors on patient care management at public hospitals. Supportive issues and barriers that influence patient care management were identified. Qualitative approach using triangulation methods through in-depth interviews, observation, field notes and records of vignettes were carried out. A total of 44 participants from two tertiary public hospitals were interviewed in this research. The data was analysed by using thematic approach. v Research indicates factors associated with patient care management were the demonstration of quality of care provided, good clinical communication, leadership skills and the understanding of culture in the health care environment. The findings from the supportive issues showed that patients were generally satisfied with the overall care given by the doctors and the hospital team of which majority of them demonstrated good leadership and management skills. However some of the barriers reported by the patients were dissatisfaction in the autonomy of making decisions and not including family members in this process. Issues on patient’s dignity and rights, culture and religion were also discovered in this research. In addition, lack of patient compliance and resources were reported as barriers in providing quality patient care. As a result situational factors have influenced the doctors’ leadership styles and many of them inadvertently become transformational leaders. To conclude, the key findings revealed the importance of medical education and leadership plan in the healthcare industry. The healthcare team, specifically the doctors should be trained as “clinical teachers” in the medical arena since they communicate and educate the patients and their families each time they provide patient care. Finally patient care management should incorporate appropriate teaching techniques using suitable resources and teaching plans in an effort to portray leadership dynamics in all situations in the wards. Efforts should also be taken by the government and the medical schools to incorporate medical education for future doctors in the medical training.